Digital Media, Participatory Culture, and Difficult Heritage: Online Remediation and the Trans-Atlantic Slave Trade. (2nd September 2015) - Morgan, Colleen; Pallascio, Pierre Marc
Abstract : A diverse and changing array of digital media have been used to present heritage online. While websites have been created for online heritage outreach for nearly two decades, social media is employed increasingly to complement and in some cases replace the use of websites. These same social media are used by stakeholders as a form of participatory culture, to create communities and to discuss heritage independently of narratives offered by official institutions such as museums, memorials, and universities. With difficult or "dark" heritage—places of memory centering on deaths, disasters, and atrocities—these online representations and conversations can be deeply contested. Examining the websites and social media of difficult heritage, with an emphasis on the trans-Atlantic slave trade provides insights into the efficacy of online resources provided by official institutions, as well as the unofficial, participatory communities of stakeholders who use social media for collective memories.